Digital Literacy, Peer Confirmity, and Juvenile Delinquency Senior High School in Keritang - Abdul Kadir; Risnawati Risnawati; Khairil Anwar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to determine the relationship 1) digital literacy and delinquency, 2) digital literacy and peer conformity, 3) digital literacy and peer conformity, 4) digital literacy and peer conformity simultaneously with delinquency of young high school students in Keritang District Indragiri Hilir Riau Riau. Using a correlational quantitative approach. The study population included 1148 students from 3 senior high schools in Keritang Indragiri Hilir Riau, a sample of 297 people used the Taro Yamane formula with the Random Sampling Technique. The data collection technique uses a closed questionnaire with a Likert model that has passed the validity and reliability tests. Data analysis techniques include, normality and linearity prerequisite tests, hypothesis testing using bivariate and multivariate correlations. The research results show 1). There is a significant relationship between digital literacy (X1) and juvenile delinquency (Y) with a negative relationship, namely the higher the adolescent's digital literacy, the lower the adolescent's delinquency. 2). There is a very significant relationship between peer conformity (X2) and adolescent delinquency with a positive relationship (Y). So that when peer conformity increases, the delinquent behavior of the adolescent also increases. 3). There is a significant simultaneous relationship between digital literacy (X1) and peer conformity (X2) with adolescent disability (Y) in the form of a significant positive relationship, that is, even though adolescents have high digital literacy, simultaneously they also have high conformity with peers. Similarly, it will have a positive relationship with juvenile delinquency.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack// This page is in Swedish Translate to English AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate Swedish to EnglishPRO Never translate Swedish Never translate ejournal.uin-suska.ac.id